THE IMPORTANT ROLE OF LEADERSHIP STYLE IN ORGANIZATIONAL CHANGE (CASE STUDY AT PT. KARWIKARYA FOREIGN TOURISTS HOUSE TANJUNG PINANG) - Satriadi Satriadi; Defis Ellmanda (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This research aims to examine the important role of leadership style in organizational change (Case Study at PT. Karwikarya Wisman Graha Tanjungpinang). Organizational change is a multifaceted process involving multiple stakeholders, from employees to leadership, and it has major implications for the overall success of the organization. The leadership style applied in today's digital era can have a significant impact on employee behavior, both positively and negatively. Through qualitative research, with library research, the author collects data by studying and understanding data that is closely related to the problem from books, theories, notes and documents. The findings found that leadership in organizations is described as important, regardless of whether the change directly impacts employees or not, highlighting the need to consider a broader organizational perspective. Members underscored the importance of servant leadership, collaborative leadership, and open leadership approaches, emphasizing empathy, humility, and adaptability in the face of change. In an era of rapid digital transformation, leadership styles are evolving to include technological competency and an understanding of digital strategy .Keywords: Leadership styles, Organizational change, Digital Transformation.